The Integrated Influence of Islamic Corporate Social Responsibility (ICSR) and Zakat Funds on The Reputation and Profitability of Islamic Banks - Pranoto, Pranoto (Riwayat: Educational Journal of History and Humanities, 2025)
This study aims to examine the effect of Islamic Corporate Social Responsibility (ICSR) and Zakat on the Reputation and Profitability of Islamic Banks in Indonesia. The ICSR index is measured based on the disclosure of 6 themes, with a value of 1 for each disclosed component and 0 if not. Profitability is proxied using Return on Equity (ROE). This study uses secondary data in the form of annual reports of Islamic Banks in Indonesia for the period 2019-2024 obtained from the official websites of each bank. The sample selection method is purposive sampling, and data analysis is carried out using multiple regression analysis. The results of the study indicate that ICSR disclosure does not have a significant effect on Reputation or Profitability. On the contrary, Zakat has a significant effect on Reputation and Profitability partially. Simultaneously, ICSR and Zakat have a significant effect on Reputation and Profitability of Islamic Banks in Indonesia.